The Diagnostic Significance of Serum Alcohol Dehydrogenase Isoenzymes and Aldehyde Dehydrogenase Activity in Prostate Cancer Patients - Orywal, Karolina; Jelski, Wojciech; Werel, Tadeusz; Szmitkowski, Maciej (Anticancer research, 2017)
The aim of this study was to investigate a potential role of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) as tumor markers for prostate cancer (PCa). Serum samples were obtained from 52 patients with PCa, 34 patients with benign prostatic hyperplasia (BPH) and 60 healthy subjects. Class III and IV of ADH and total ADH activity were measured by the photometric method. For measurement of class I and II ADH and ALDH activity, the fluorometric method was employed. Significantly higher total activity of ADH, ADH III and ADH IV were found in the sera of both, PCa and BPH patients compared with healthy individuals. The diagnostic sensitivity for ADH III activity was 94.2%, specificity 100%, PPV (positive predictive value) and NPV (negative predictive value) were 100% and 95.2% respectively. Area under receiver-operating characteristics (ROC) curve for ADH III activity was 0.993. The results suggest a potential role of ADH III activity as a parameter included in the panel of markers for PCa.